Impact of coastal development on mangrove distribution in Kuantan, Pahang - Saad, Shahbudin; Ahmad, Zuhairi; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal (2009)
The mangrove ecosystem is one of the most productive ecosystems in the world. In Malaysia, mangroves cover about 52% of the total length of the Malaysian coastline. Kuantan is situated at the east-coast of Peninsular Malaysia, covering 2159.90 ha of mangroves which consist of 11 species and dominated by Sonneratia alba and Rhizophora mucronata. The massive development activities at Kuantan have given enormous pressure to the residential and industry purposes, followed by aquaculture and other related activities. In order to ensure the survivability of mangroves and sustainable coastal zone development, a continuous monitoring of mangroves over time period is essential. Based on the above perspective, a study has been conducted by using Landsat-5 TM data of Kuantan mangroves for the past 20 years. The study reveals that the total area of mangroves at Kuantan in 1989 was 2885.60 ha. Besides, the periodic supervised classification has shown that mangroves have been degraded more than 725.70 ha. Thus, the rapid development in Kuantan especially along the coast and riverbank areas could be alarming and major threats for the sustainable development of mangroves in Kuantan estuary.